Evaluation instrument for e-government websites. (8th June 2007) - Henriksson, Anders; Yi, Yiori; Frost, Belinda; Middleton, Michael
An instrument for evaluating the quality of government websites is described. It takes the form of a questionnaire resident within spreadsheet or database software so that an automatically determined evaluation may be indicated following input of data. The 106 questions included are derived from previous research regarding significant components of successful websites, along with interviews with developers of portals at different levels of Australian government. The instrument may be easily tailored to accommodate varying requirements at different levels of government, and used as a basis for extended internal evaluation of their own websites by agencies. The instrument also embodies explanations of the survey questions that are asked, along with advice on how to determine sought-after information from sites.